Generating in vitro solid tumor models on gelatin-alginate scaffolds - Nho Thuan Nguyen; Vu Nguyen Doan; Ha Le Bao Tran (Vietnam Journal of Science, Technology and Engineering, 2018)
In recent years, three-dimensional (3D) in vitro tumor models have become more common in cancer research across the world. Selecting scaffolds, seeding cells into the scaffolds, and culturing them are pivotal for the morphologies and proliferation of cancer cell lines. Therefore, this experience has developed a 3D tumor model based on co-culturing MCF-7 cells and fibroblasts (3:1) into gelatin-alginate scaffolds (3x3x5 mm3). Quantity, proliferation, and morphologies of tumors were evaluated through cell yield on a scaffold, enzymatic assay, cell number, hematoxylin and eosin stains (H&E), and scanning electron microscope (SEM). The results indicate that the complex of MCF- 7 cell lines and fibroblasts in scaffolds proliferated and increased in terms of cell mass number and cell mass size. Their morphologies align with those of the in vivo figures demonstrated previously. This research facilitates new opportunities for the study of cancer biology and drug screening in Vietnam.